Assessment of occupational health hazards and associated morbidities in sanitation workers of a metropolitan city in India: a cross-sectional study - Gada, Nilam P.; Shukla, Rushikesh; Kumar, Pratyush; Shah, Kunal; Abhishek, Kumar; Sarkar, Manali; Malhotra , Geeti; Panchawagh, Suhrud; Pathak, Swanand (International Journal Of Community Medicine And Public Health, 2023)
Background: Rapid economic development in emerging countries has accelerated urbanisation, resulting in a rise in urban population as well as sanitation issues such as garbage buildup, clogged sewers, and unhygienic streets. Sanitation employees’ health and safety are impacted by increasing workloads and dangers. Numerous health hazards are highlighted in studies, including those related to their gastrointestinal system, lungs, musculoskeletal system, and infectious disorders. Concerns include psychological issues and cancer as well. Methods: Data from sanitation employees who participated in rotary screening and health checkup activities in Mumbai were analysed in this retrospective cross-sectional research. The study collected demographic information, a self-designed questionnaire on alcohol and cigarette use, and clinical characteristics such blood pressure and haemoglobin levels from participants after they gave informed written consent. Results: The participants in this retrospective observational research from Mumbai, India, included 793 sanitation employees in total. Age, gender, and tobacco/alcohol use were among the participant variables and targeted results that we looked at. The significant results obtained were cataract on one side 17/793, erythroplakia 1/793 and leukoplakia 26/793. Conclusions: It is essential to acknowledge their accomplishments and provide greater assistance. Waste disposal is difficult in poor countries because of the prevalence of organic waste. To protect employees, immediate action and the appropriate protective equipment are required.